Hippotherapy as a way of improving motor performance in juveniles with infantile cerebral palsy - Sławomir Kozioł; Piotr Wróbel (University of Applied Sciences in Tarnow, Poland, 2022)
Animals have accompanied man for thousands of years and their role in human life has seriously evolved. Man had power over domesticated animals and decided about their fate, they were used as a means of transport and helped humans with the farming. There is a group of animals, known as companion animals, which are ranked high in human life. Nowadays, animals are more frequently utilized in different animal-assisted therapies. Hippotherapy as a therapeutic intervention exerts serious influence on those participating in its sessions, and it affects all interpenetrating spheres of human life. Therapeutic effects of horse-riding were already known in 400 B.C. Hippocrates claimed that horse-riding exerted positive effect on treating certain health conditions. Equine therapists, over the years, have noticed significant benefits to their clients resulting not only from the nature of a horse but also from its unique ambulation. One can say that a horse during a therapeutic session becomes a precise stimulator of movement. Thanks to a similar way of ambulation in man and in a horse, during a horse riding session the rider's pelvis, trunk and the shoulder girdle are made to move according to the physiological pattern of human ambulation, so a person with motor disorders has a chance to learn proper human gait pattern without walking.